2015
DOI: 10.1007/s00439-015-1627-5
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of mutations and genotype–phenotype analysis in Noonan syndrome patients with RIT1 mutations

Abstract: RASopathies are autosomal dominant disorders caused by mutations in more than 10 known genes that regulate the RAS/MAPK pathway. Noonan syndrome (NS) is a RASopathy characterized by a distinctive facial appearance, musculoskeletal abnormalities, and congenital heart defects. We have recently identified mutations in RIT1 in patients with NS. To delineate the clinical manifestations in RIT1 mutation-positive patients, we further performed a RIT1 analysis in RASopathy patients and identified 7 RIT1 mutations, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 47 publications
7
91
0
1
Order By: Relevance
“…The encoded protein is involved in a wide variety of cellular processes, including cell proliferation, differen-tiation, and survival. It has been shown that different pathogenic variants in the RIT1 gene cause autosomal dominant Noonan syndrome through a gain-of-function mechanism resulting in increased RAS/MAPK signaling [Bertola et al, 2014;Gos et al, 2014;Milosavljević et al, 2016;Yaoita et al, 2016]. Recent reports have demonstrated that copy number variations containing disease-causing genes of RAS/MAPK pathway may be a pathogenetic mechanism for the etiology of RASopathies or related disorders [Graham et al, 2009;Luo et al, 2012;Chen et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…The encoded protein is involved in a wide variety of cellular processes, including cell proliferation, differen-tiation, and survival. It has been shown that different pathogenic variants in the RIT1 gene cause autosomal dominant Noonan syndrome through a gain-of-function mechanism resulting in increased RAS/MAPK signaling [Bertola et al, 2014;Gos et al, 2014;Milosavljević et al, 2016;Yaoita et al, 2016]. Recent reports have demonstrated that copy number variations containing disease-causing genes of RAS/MAPK pathway may be a pathogenetic mechanism for the etiology of RASopathies or related disorders [Graham et al, 2009;Luo et al, 2012;Chen et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, nine different missense mutations in RIT1 were reported in 17 of 180 individuals with NS with no mutations in the previously known NS genes [Aoki et al, 2013]. Others [Bertola et al, 2014;Chen et al, 2014;Gos et al, 2014;Justino et al, 2015;Koenighofer et al, 2016;Yaoita et al, 2016)] described additional patients with mutations in RIT1. In line with the observations in other NS associated genes, functional studies showed that mutant RIT1 results in an enhanced signaling activity of the RAS-MAPK pathway [Aoki et al, 2013;Chen et al, 2014;Koenighofer et al, 2016;Yaoita et al, 2016].…”
Section: Introductionmentioning
confidence: 98%
“…Others [Bertola et al, 2014;Chen et al, 2014;Gos et al, 2014;Justino et al, 2015;Koenighofer et al, 2016;Yaoita et al, 2016)] described additional patients with mutations in RIT1. In line with the observations in other NS associated genes, functional studies showed that mutant RIT1 results in an enhanced signaling activity of the RAS-MAPK pathway [Aoki et al, 2013;Chen et al, 2014;Koenighofer et al, 2016;Yaoita et al, 2016]. The aim of our study was to further delineate the clinical phenotype by presenting two patients with novel phenotypic manifestations of a RIT1 mutation and by providing an overview of the current literature on RIT1.…”
Section: Introductionmentioning
confidence: 99%
“…6, E and F). The A57G and Y89H mutations were highly activated in the RBD pulldown, and have been shown to enhance activation of ERK (5,8) and ELK (4,9).…”
Section: Structural Considerations Of Rit1 Disease-associatedmentioning
confidence: 99%
“…ERK (5), and activation of ELK (4,9). In addition to fast nucleotide exchange, the S35T mutant also exhibited reduced GTPase activity, which is likely related to perturbation of the Mg 2ϩ ion.…”
Section: Structural Considerations Of Rit1 Disease-associatedmentioning
confidence: 99%